A Low‐Cost and Facile Method for the Preparation of Fe‐N/C‐Based Hybrids with Superior Catalytic Performance toward Oxygen Reduction Reaction. Issue 8 (1st March 2019) - Zhang, Yanpei; Wang, Nan; Jia, Ning; Wang, Jing; Sun, Jie; Shi, Feng; Liu, Zong‐Huai; Jiang, Ruibin
Abstract: Fe‐N‐doped graphitic carbon materials exhibit high efficiency and durability for oxygen reduction reaction (ORR). Although iron has relatively low price, the precursors for carbon and nitrogen used in previous studies have relatively high cost. Here reported is the preparation of highly efficient Fe‐N/C‐based ORR electrocatalysts by use of low‐cost urea as the precursors. Fe‐N/C‐based hybrids are prepared through a two‐step pyrolysis. During the first‐step pyrolysis, the precursors convert into g‐C3 N4 with Fe located into the sixfold cavities, which ensures the relatively uniform distribution of Fe. The second‐step pyrolysis converts Fe‐g‐C3 N4 into Fe‐N/C‐based hybrids which contain multiple types of active components, Fe moieties (FeC x N y or FeN x ), Fe and Fe3 N nanoparticles, for ORR. The obtained Fe‐N/C‐based hybrids display a superior electrocatalytic performance for ORR with an onset potential of 0.940 V and half‐wave potential of 0.810 V versus reversible hydrogen electrode, which are comparable to those of Pt/C at the same catalyst loading. The hybrids show higher tolerance to methanol and much greater long‐term stability than commercial Pt/C. The findings provide a cost‐effective approach for the preparation of high efficient and stable electrocatalysts for ORR and will be very helpful to the development of electrochemical energy storage and conversion. Abstract : Fe‐N/C‐based nanohybrids are prepared through a two‐step pyrolysis by use of low‐cost urea as precursors. The obtained Fe‐N/C‐based hybrids contain three types of oxygen reduction reaction (ORR) active components, homogeneously distributed coordinating Fe moieties (FeC x N y or FeN x ) and Fe and Fe3 N nanoparticles encapsulated with defect‐free N‐doped graphitized carbon. The hybrids exhibit very high catalytic activity, stability, and methanol tolerance for electrocatalytic ORR.